Conserving and Extracting Nature: Environmental Politics and Livelihoods in the New "Middle Grounds" of Amazonia. (29th June 2020) - High, Casey; Oakley, R. Elliott
Abstract: While Amazonian people are well known in anthropology for challenging modernist ideas of "nature, " extractive industries and development projects have placed them at the forefront of conflicts around the environment. In 1995 Beth Conklin and Laura Graham identified these interfaces as increasingly translocal, leading them to describe an emerging "middle ground" that situates indigenous Amazonian people and Western environmentalists as natural allies. In recognizing twenty‐five years of the Journal of Latin American and Caribbean Anthropology and Conklin and Graham's seminal article, this Jubilee special issue revisits the middle ground concept in terms of intensifying interface relationships in Amazonia. In conceptualizing the "new middle grounds" of conservation and extractive economies, we explore processes of accommodation, partnership, contestation, and potential domination that are grounded in local perspectives and practices. In this way we aim to extend the focus on radical difference in arguments about Amazonia to recognize the complex ways in which indigenous experience is also deeply embedded in Latin American culture and politics. [environmental politics, extractive economies, middle ground, conservation, livelihoods, Amazonia] Resumen: Tanto como los pueblos de la Amazonía son conocidos en antropología por haber desafiado ideas modernistas de "la naturaleza, " industrias extractivas y varios proyectos de desarrollo los colocan al frente de conflictos acerca del medio ambiente. En 1995, Conklin y Graham identificaron que estas interfazes son cada vez mas translocales, provocando a describir un emergente "middle ground" que ubica los pueblos indígenas de la Amazonía y los ambientalistas occidentales como aliados naturales. Reconociendo veinticinco años de la Journal of Latin American and Caribbean Anthropology y del artículo seminal de Conklin y Graham, este "jubilee special issue" reconsidera el concepto "middle ground" en el contexto de nuevos y emergentes relaciones en la Amazonía contemporánea. Al conceptualizer los "new middle grounds" de conservación y economias extractivas, investigamos los procesos de acomodación, coloboración, oposición, y posible dominación basadas en perspectivas y prácticas locales. De esta manera nos proponemos extender discusiones de las diferencias radicales en la Amazonía para reconocer también las maneras complejas en que las experiencias indígenas están profundamente integradas en la cultura y política latinoamericana.